2020
DOI: 10.1111/his.14081
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of tumour apolipoprotein D independently predict poor outcome in breast cancer patients

Abstract: Aims: Apolipoprotein D (ApoD) is a protein that is regulated by androgen and oestrogen, and is a major constituent of breast cysts. Although ApoD has been reported to be a marker of breast cancer, its prognostic importance in invasive breast cancer is unclear. The aim of this study was to investigate the relationship between ApoD protein expression, oestrogen receptor-a (ERa) expression and androgen receptor (AR) expression in predicting breast cancer outcome. Methods and results: ApoD levels were measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…A recent study performed on a cohort of patients diagnosed with invasive ductal breast carcinoma shows that ApoD could be an independent predictor of metastasis free survival and overall survival in invasive breast cancer. Increased ApoD expression was associated with poor patient outcome (Jankovic-Karasoulos et al, 2020), a result shared with another research team studying breast cancer outcomes in patients over the age of 70 (Soiland et al, 2009). It is important to note that patients in this last study were under tamoxifen therapy, a drug used to treat estrogen receptor-positive tumors (Harbeck et al, 2019).…”
Section: Role In Cancermentioning
confidence: 60%
“…A recent study performed on a cohort of patients diagnosed with invasive ductal breast carcinoma shows that ApoD could be an independent predictor of metastasis free survival and overall survival in invasive breast cancer. Increased ApoD expression was associated with poor patient outcome (Jankovic-Karasoulos et al, 2020), a result shared with another research team studying breast cancer outcomes in patients over the age of 70 (Soiland et al, 2009). It is important to note that patients in this last study were under tamoxifen therapy, a drug used to treat estrogen receptor-positive tumors (Harbeck et al, 2019).…”
Section: Role In Cancermentioning
confidence: 60%
“…In this study, we further analyzed the DEmRNAs associated with FAT2 mutations and constructed a 4-mRNA prognostic signature of GC (APOD, STK32A, SVEP1, NPTX1). Many studies have demonstrated that APOD expression is correlated with various tumors, such as breast cancer and colorectal cancer, and is significantly associated with GC risk assessment [28][29][30]. STK32A participates in cellular homeostasis, cell-cycle modulation, and phosphorylation of transcription factors, and can modulate the invasion and metastasis of non-small cell lung cancer [31].…”
Section: Discussionmentioning
confidence: 99%
“…CD59 is highly expressed in several cancer cell lines and tumor tissues and regulates the function, infiltration, and phenotypes of various immune cells in the tumor microenvironment ( 28 ). APOD may be a potential therapeutic target for tumor angiogenesis by suppressing PI3K-Akt-eNOS signaling, an essential pathway regulating angiogenesis ( 29 , 30 ).…”
Section: Resultsmentioning
confidence: 99%